Ecological Fire Retardant for Wood Impregnation - Canosa, Guadalupe (2023)
In this research, it was study Pinus elliottii wood impregnated with 5 and 10% whey proteins suspensions to improve its behavior against fire action. The good results obtained either in Thermogravimetric Analysis, in “Intermittent flame of a Bunsen burner test” and in Oxigen Index test allowed concluding that treated wood showed increased fire resistance. This would be based on the fact that the water adsorbed by the proteins could partially dissipate during combustion and, in addition, dilute the volatile products generated forming an oxygen-poor atmosphere, near the material. In addition, the thermal energy released during conflagration takes longer to reach the substrate due to more char is formed in the impregnated wood, acting as thermal insulator.